Revamp the Power Consumption in MANET by designing EPARDA routing Protocol (International Journal of Engineering and Computer Science, 2017)
In wireless networks, the communication link between the nodes is changeable, since the qualities of the wireless links change their states heavily. Mobile ad hoc network (MANET) is an infrastructure less network; its nodes are mobile in nature. So that, the mobile device needs more battery power due to the nodes moves in a rapid form of nature, so power feeding is the major issues in MANET. The data packets transmit from root node to the terminal node through some intermediate nodes. The draining of few nodes due to power weakening might cause the entire MANETs services disconnected. So that to improve the power consumption in MANET, we improvise the EPAR-DA [Efficient Power Aware Routing with Data Aggregation] algorithm, by adding the aggregation process with EPAR algorithm. The EPAR algorithm describes the track route and chooses the path based on the energy downed to convey the data packets from source to the destination through sub-terminal nodes. EPAR estimate all lowest hop energy of the paths and then select the maximum lowest hop energy to transfer the data packet. And through the data aggregation process, data are aggregated and transmitted in certain periodic interval to reduce the power. EPAR algorithm is an on-demand source routing protocol that uses battery lifespan anticipation. By evaluating ad hoc network routing protocols, EPAR-DA consumes less energy when compare to other protocols like MTPR [Minimum Transmission Power Routing], and DSR [Dynamic Source Routing] in different network scales. The total energy using up of the MANET is reduced by EPAR-DA and achieves a good packet delivery ratio especially for high load networks.